Unveiling The Dark Side of Transformational Leadership: Examining Leader Dependency and Its Influence on Organizational Dynamics - Andrianto Iskandar (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2024)
While transformational leadership is often praised for its capacity to inspire change and drive innovation, this paper aims to delve into the less-explored negative repercussions of this leadership style, particularly in terms of fostering excessive leader dependency. The study examines how leader-centric dynamics may compromise team autonomy, stifle creativity, and lead to organizational in efficiencies over time. Through a mixed-method approach involving case studies and survey data from multinational organizations, this research unveils that transformational leader, while empowering, can unintentionally cultivate a reliance on their vision and guidance, thereby constraining the cultivation of self-sustaining leadership within teams. The findings underscore the significance of striking a balance between transformational leadership and autonomy-promoting practices to steer clear of dependency traps. This paper contributes to the expanding body of literature on leadership dynamics by offering a nuanced comprehension of the potential risks associated with transformational leadership. Furthermore, it discusses the implications for leadership development, organizational design, and employee empowerment.